The burden of back pain on hospital staff in a maximum care facility in Germany – a survey - Josina Straub; Melanie Ardelt; Kristina Gerhardinger; Lisa Klute; Jonas Krueckel; Markus Rupp; Volker Alt; Siegmund Lang (Brain and Spine)
Purpose: Back pain is a prevalent musculoskeletal condition affecting individuals across various professions. It is a significant cause of disability and reduced quality of life. The aim of this study was to determinate the prevalence of back pain and identify its associated risk factors among clinical staff members. Methods: This study examines back pain among hospital-staff at a maximum-care hospital in Germany through a questionnaire distributed to all employees at a University Hospital between September and December 2023. Results: A total of 739 employee questionnaires were returned and evaluated, comprising 508 fully completed and 231 partially completed questionnaires. Seventy-seven percent of participants were female, and the average age was 40.5 years. Back pain-related reduced work performance was reported by 57.5 %. Lifetime lower back pain was indicated by 72.1 %. Mean pain ratings on the VAS were 7.5 ± 2.2 for lifetime pain and 6.2 ± 2.2 for the last 12 months. Female gender (OR = 1.5; p = 0.003), living in a partnership (OR = 1.4; p = 0.02), chronic illnesses (OR = 6.4; p = 0.01) and excessive workload (OR = 3.0; p = 0.05) were identified as risk factors, whereas membership in a sports club (OR = 0.55; p = 0.05) was identified as preventive factor. Participants that reported an aggravation of their back pain the COVID-19 pandemic were 6.4 times likely to report back pain during the last 12 months (p = 0.01). Conclusion: Back pain is a widespread condition among healthcare workers, leading to reduced performance and significant healthcare utilization. Employers should prioritize preventive measures and workplace ergonomics to mitigate this burden and enhance employee well-being and productivity. Level of evidence: III, survey.